Vehicle accident alert system using GPS and GSM / Deanial Fikri Mat Desa - Mat Desa, Deanial Fikri (College of Computing, Informatics, and Mathematics, 2024)
This paper presents the design and implementation of a Vehicle Accident Alert System (VAAS) leveraging advanced technologies including the MPU6050 accelerometer, GPS Neo-6M module, TTGO ESP32 microcontroller, SIM800H GSM module, and an alert button. The VAAS aims to enhance road safety by promptly detecting and reporting vehicle accidents to emergency responders and designated contacts. The MPU6050 accelerometer detects sudden changes in acceleration indicative of a collision, while the GPS Neo- 6M module provides accurate location data. The TTGO ESP32 microcontroller serves as the central processing unit, coordinating communication between components and executing accident detection algorithms. Upon detection, the system utilizes the SIM800H GSM module to send automated alerts via SMS or call to emergency services and pre-registered contacts. Additionally, an alert button allows users to manually trigger emergency notifications. This abstract highlights the integration of cutting-edge technologies to create an efficient and reliable system for mitigating the consequences of vehicular accidents and facilitating rapid emergency response.